UMPSA strengthens educational ties with Kazakhstan - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
KUALA LUMPUR, 27 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is set to enhance its academic and research collaboration with Kazakhstan following a visit to the Embassy of Kazakhstan in Malaysia. Led by UMPSA’s Vice-Chancellor, Professor Dr. Yatimah Alias, the engagement marked a significant step in fostering stronger ties between the two nations in higher education.